La universidad y el Cabildo eclesiástico de México: siglo XVI - Castillo Flores, José Gabino (2017)
This article examines the role of the University of Mexico in the formation of the Ecclesiastical Cabildo of Mexico City in the second half of the 16th century, since it was in its classrooms that the learned men who would occupy key positions in the secular and ecclesiastical government of the kingdom of New Spain were groomed. They were the sons of the conquistadors and the earliest colonists who settled in the Indies. Thanks to the university, a local bureaucracy was created that would shape and consolidate the principal corporate bodies of the kingdom, including the Ecclesiastical Cabildo of Mexico. The text elucidates how the close relationship between these two corporate bodies benefitted the project of the secular Church and functioned to anchor the population of Spanish origin in New Spain.